2008
DOI: 10.1017/s095026880800054x
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected discovery of a focus of hepatitis C virus genotype 5 in a Syrian province

Abstract: Genotype 5 (G5) was initially discovered and is still mainly diagnosed in South Africa. No cases of G5 have ever been reported from the Middle East countries. The aim of the study was to determine the hepatitis C virus (HCV) genotype distribution in Syria and the prevalence of G5 in this country. Genotyping of HCV was performed in 636 consecutive HCV patients referred to eight medical centres in Syria over a 3-year period. Genotype 4 was the most frequent genotype (375 patients, 59%) followed by genotype 1 (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Habbal and Monem (27) argued that, despite the reported association of genotype D with poor response to interferon-based therapeutic regimens, interferon alpha is routinely prescribed as the first-line therapy in hepatitis B in the Syrian Arab Republic, according to the national guidelines (21). Similar arguments are applicable to the treatment of chronic HCV, in which genotype 5 has been reported (29,30).…”
Section: National Policies On Hepatitis In the Syrian Arab Republicmentioning
confidence: 68%
“…Habbal and Monem (27) argued that, despite the reported association of genotype D with poor response to interferon-based therapeutic regimens, interferon alpha is routinely prescribed as the first-line therapy in hepatitis B in the Syrian Arab Republic, according to the national guidelines (21). Similar arguments are applicable to the treatment of chronic HCV, in which genotype 5 has been reported (29,30).…”
Section: National Policies On Hepatitis In the Syrian Arab Republicmentioning
confidence: 68%
“…In Syria, HCV‐5 represents 10% of all HCV genotypes and is almost exclusively found in the north of Syria in the province of Aleppo, with half of the cases originating from Azaz, a small city of 30 000 inhabitants close to the Turkish border. But no cases of HCV‐5 have ever been reported in Turkey or any other countries neighbouring Syria and there is no immigration from Africa to Syria (16). However, a recent phylogenetic analysis of Syrian samples showed that the Syrian samples are clustered in the South African group (unpublished data).…”
Section: Epidemiologymentioning
confidence: 99%
“…The cause of transmission was only known in 30%, blood transfusion being reported in 14% of the patients. Cirrhosis was present in 23% of the patients (16).…”
Section: Natural Historymentioning
confidence: 99%
“…This was an individual patient data metaanalysis (including 38 HCV-5 patients from 2 randomized trials), mainly limited by the inclusion of relapsers and patients receiving additive treatments (amantadine). [5][6][7]19 Mode of transmission remained largely unexplained, although iatrogenic and intrafamilial routes are probably major sources of HCV-5 infection in our region. 7 In contrast, in a recent retrospective study including 49 patients from Syria (6 of them treated with standard interferon in the combination scheme), a lowest SVR of 49% has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 On the basis of the phylogenetic analysis of viral genomic sequences, at least 6 major HCV genotypes and more than 70 subtypes have been identified. [5][6][7][8][9][10][11] In Greece, prevalence of HCV-5 has been estimated to be 0.4% to 1.9%. 3,4 However, sporadic presence of HCV-5 has been reported in other parts of the world including France, Belgium, Canada, Syria, Spain, Germany, and Brazil.…”
mentioning
confidence: 99%